Microwave-assisted synthesis of NiS2 nanostructures for supercapacitors and cocatalytic enhancing photocatalytic H2 production - Pang, Huan; Wei, Chengzhen; Li, Xuexue; Li, Guochang; Ma, Yahui; Li, Sujuan; Chen, Jing; Zhang, Jiangshan (Scientific reports, 2014)
Uniform NiS 2 nanocubes are successfully synthesized with a microwave-assisted method. Interestingly, NiS 2 nanocubes, nanospheres and nanoparticles are obtained by controlling microwave reaction time. NiS 2 nanomaterials are primarily applied to supercapacitors and cocatalytic enhancing photocatalytic H 2 production. Different morphologies of NiS 2 nanostructures show different electrochemical and cocatalytic enhancing H 2 production activities. Benefited novel nanostructures, NiS 2 nanocube electrodes show a large specific capacitance (695 F g −1 at 1.25 A g −1 ) and excellent cycling performance (the retention 93.4% of initial specific capacitance after 3000 cycles). More importantly, NiS 2 nanospheres show highly cocatalytic enhancing photocatalytic for H 2 evolution, in which the photocatalytic H 2 production is up to 3400 μmol during 12 hours under irradiation of visible light (λ>420 nm) with an average H 2 production rate of 283 μmol h −1 .